SISTEM PERBANKAN KONVENSIONAL DALAM PERSPEKTIF FIKIH MUAMALAT - Ayu Sandra Intan Aprilia; Luluk Safitri (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2020)
In muamalah, there are two transaction parties who have the same position both in rights and obligations. However, the impression generated from the banking law regulates and protects banks as financial institutions. Meanwhile, the position of the customer does not get an adequate portion in the law so that the impression that the customer in an agreement is more likely to be an object rather than a subject. The principle of muamalah is actually implemented in Indonesian banking law, as found in several articles in the banking law, but it does not mean it is implemented. This means that when the law is drafted it is strongly suspected that it does not carry a special message to include muamalah principles which are implemented in banking law because muamalah principles are universal which are upheld by human values.